A Study of the Value of the Human Voice in the Context of Body Embodiment - Liu Li-ping (SHS Web of Conferences, 2023)
The idea that “the human voice has a feature of embodiment” was proposed by Mr. Xue Yibing, a Chinese researcher who belongs to a member of the Institute of Music, China Academy of Art. Such a no-tion is not only strange but also familiar. In this context, this paper will borrow the concept of "the origin of musical beauty is the human voice" and combine it with Husserl’s view of "To the things themselves" in phenomenology. Under this circumstance, the embodiment of the human voice would be understood from the human body and sound itself, and the existence value and aesthetic value of the human voice it brings, that is, from the current value, it proves the subjectivity, spiritual embodiment and emotional preservation of human beings; from the aesthetic value, it recognizes non-real objects, brings dynamic manifestation and embodies aesthetic imagery. The inspiration of the human voice in contemporary art creation is further ob-tained: the understanding of tradition and innovation in the human voice, the use of voice to integrate the single and multiple, the human voice to carry the individual and society, the human voice to coordinate the reality and transcendence, which gives the human voice in the new era more profound connotation and sig-nificance.